Sumarização e extração de conceitos de notas explicativas em relatórios financeiros: ênfase nas notas das principais práticas contábeis - Cagol, Adriano (Universidade do Vale do Rio dos Sinos, 2017)
Financial statements present the financial performance of companies and are an important tool for analyzing the financial and equity situation, as well as for making decisions of investors, creditors, suppliers, customers, among others. These are listed explanatory notes that describe in detail how practices and policies of accounting methods of the company. Depending on the objectives, a correct analysis of the situation of a company on the financial statements is not possible without an interpretation and analysis of the footnotes. However, despite the importance, an automatic analysis of the footnotes to the financial statements is still an obstacle. In view of this deficiency, this work proposes a model that applies text mining techniques without the sense of identifying the main methods of calculating the accounting accounts, the reports in the footnotes, with concept extraction, as well as generating a summary that contemplates the main idea of these, through summarization. A concept extraction algorithm and six summarization algorithms are applied in financial statements of companies of Brazilian Securities and Exchange Commission. The work shows that concept extraction generates promising results for the identification of the method of calculating the accounting account, since it presents a 100% accuracy in the footnote of inventory and property, plant and equipment, and accuracy of 96.97% in the footnote on revenue recognition. In addition, it evaluates the algorithms for summarization with the ROUGE measure, pointing out the most promising ones, especially LexRank, which in general obtained the best evaluations.
Keywords: Mineração de textos; Sumarização automática; Extração de conceitos; Notas explicativas; Demonstrações financeiras; Demonstrações contábeis; Text mining; Automatic summarization; Concepts extraction; Footnotes; Financial statements; Accounting statements; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação